Pendekatan Sistematis terhadap Total Quality Management: Analisis Tematik Penerapan Standar Mutu dan Dampaknya terhadap Kualitas Layanan - Noer sulistiawati; Milda Ajeng Dea R; Sa’adah Sa’adah; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Quality management and Total Quality Management (TQM) have become critical issues in both education and industry because they are directly related to service quality, process efficiency, and customer satisfaction. The rise of global competition demands organizations to implement a quality system that not only focuses on technical standards, but also integrates a comprehensive quality culture. This article aims to answer the research question regarding how the application of quality standards and TQM affects the quality of organizational management and the benefits produced for both academics and practitioners. The research method uses a qualitative approach with a literature review (LR) model. Data were obtained from 20 scientific articles published between 2020 and 2025 through Google Scholar and Publish or Perish (PoP) using the keywords “quality management, standard, benefits, TQM.” After the screening process, five articles were selected for in-depth analysis. The results of the analysis reveal three main findings: (1) quality standards serve as a fundamental basis for maintaining quality consistency, (2) the implementation of TQM is proven to be flexible and applicable across various sectors, and (3) the benefits of TQM include improved service quality, process efficiency, and customer satisfaction. The conclusion of this synthesis highlights that the application of TQM is not merely a technical strategy, but also shapes a sustainable organizational culture. Future studies should further explore the integration of TQM within the context of digitalization and educational innovation.